Endogenous opioids in the olfactory tubercle and their roles in olfaction and quality of life - Murata, Koshi; Maegawa, Ayako; Imoto, Yoshimasa; Fujieda, Shigeharu; Fukazawa, Yugo (Frontiers in Neural Circuits, 2024)
Olfactory dysfunctions decrease daily quality of life (QOL) in part by reducing the pleasure of eating. Olfaction plays an essential role in flavor sensation and palatability. The decreased QOL due to olfactory dysfunction is speculated to result from abnormal neural activities in the olfactory and limbic areas of the brain, as well as peripheral odorant receptor dysfunctions. However, the specific underlying neurobiological mechanisms remain unclear. As the olfactory tubercle (OT) is one of the brain’s regions with high expression of endogenous opioids, we hypothesize that the mechanism underlying the decrease in QOL due to olfactory dysfunction involves the reduction of neural activity in the OT and subsequent endogenous opioid release in specialized subregions. In this review, we provide an overview and recent updates on the OT, the endogenous opioid system, and the pleasure systems in the brain and then discuss our hypothesis. To facilitate the effective treatment of olfactory dysfunctions and decreased QOL, elucidation of the neurobiological mechanisms underlying the pleasure of eating through flavor sensation is crucial.